First, we have to start balancing the equation:
H2O2 + FeSO4 + H2SO4 → Fe2(SO4)3 + H2O
we can see that the number of H atoms on the left side is 4 and on the right side is 2 so we have to make the number of H atoms are equal on both sides
so, we will put 2H2O instead of H2O
H2O2 + FeSO4 + H2SO4 → Fe2(SO4)3 + 2H2O
we can see that number of O on the left side is 10 and on the right side 14
so we will put 2 FeSO4 instead of FeSO4
H2O2 + 2FeSO4 + H2SO4 → →Fe2(SO4)3 + 2H2O
∴ the coefficients of the reactants and products will be in order 1 2 1 1 2